Cross subsidy model for community transformation: Jain University social responsibility in India. (2018) - Kandhadai, Ravi; Chander, P.
Jain Vidya Niketan (JVN) in Kanakpura, Bangalore, India, is an opportunity school for the rural poor offering access to high quality education which would have otherwise been inaccessible to them. The JVN cross subsidy model is unique though it reflects in parts many theoretical concepts, practices and elements such as those of Carroll's (1979) pyramid model, the Intersecting Circles model, the Concentric Circles model (Aviva Geva, 2008) and the Impact-based USR model (Belyaeva, 2015). It is in this light the JVN case as a viable example of university social responsibility is presented. This paper also proposes a synthesised model called 'Model of auspicious vision for all' with innovative factors namely emotional capital and spiritual capital in addition to economic, ethical and philanthropic considerations.